Oxidation of Ti-6Al-4V during wire and arc additive manufacture - Caballero, Armando; Ding, Jialuo; Bandari, Yashwanth K.; Williams, Stewart W. (Cranfield University, 2019)
Owing to the high reactivity of titanium with oxygen at high temperatures, oxidation is often observed during wire and arc additive manufacture (WAAM) of Ti-6Al-4V. As a sign of oxidation, discoloration of titanium components built by WAAM is usually observed, due to the formation of a thin oxide scale on the surface. This generally constitutes a major concern from the end user. Together with the oxide scale, oxidation also produces the formation of a brittle oxygen-enriched layer near the surface (Alpha Case) and it can be detrimental in terms of mechanical properties. Hence, it is of major interest to investigate the influence of surface oxidation on the bulk material property of WAAM of Ti-6Al-4V and understand the oxidation process during WAAM deposition. In this work, oxidation of titanium during WAAM was investigated to determine the mechanisms and main process parameters controlling this phenomenon. To address this, plasma-transferred arc and wire deposition samples were manufactured by changing either deposition parameters or oxygen levels in the fusion atmosphere. Subsequently, samples were characterized by means of visual inspection, optical microscope, scanning electron microscope, and tensile mechanical testing. For any containing level of oxygen in the shielding environment, it was found that if temperatures are high enough and exposure times long, oxidation of titanium is observed. In addition, it was possible to determine that oxidation is more significant in the region of the first deposited layers. The maximum depth of Alpha Case was found to be 200 μm for the samples built with higher current (220 A) and wider oscillation width. Tensile testing revealed that increasing 40 times the oxygen levels in the shielding environment does not affect the tensile strength significantly.
Keywords: Additive manufacture; titanium; alpha case; oxidation; oxide scale